Analisis Pemahaman Konsep Siswa pada Pembelajaran Larutan Elektrolit dan Non-Elektrolit dengan 8E Learning Cycle - Fitriyani, Dewi; Rahmawati, Yuli; Yusmaniar, Yusmaniar (Jurnal Riset Pendidikan Kimia (JRPK), 2019)
This study was aimed to develop students’ conceptual understanding in material “electrolyte and non-electrolyte solution” using 8E Learning Cycle model. The study involved 36 students in 10th grader of Math and Science Studies senior high school in Jakarta. Data collection techniques used was interview, concept understanding test, reflective journal and students’ worksheet. Based on the research, the result shows that by using 8E Learning Cycle model , the students’ understanding toward the concepts in sub-material of the solution characteristics and the nature of the solution are increased. Referring to the graph, students’ concept understanding increased to 96% in the sub-material of the characteristics of the solution. Besides, the students’ understanding toward sub-material of the nature of solution increased to 80%. The biggest misconception occurs at the explore stage, this is caused by the students initial knowledge. Students are able to group the electrolyte and non-electrolyte solutions correctly based on the ionization of the solution, but the students are not able to connect the electrolyte and non-electrolyte solutions to the type of bond. In learning process, 8E learning cycle model is not only used as instrumental in developing students' concepts understanding, but also this model plays a role in developing the students’ communication skill and collaboration skill in chemistry learning. Keywords 8E learning cycle model, conceptual understanding, electrolyte and non-electrolyte solutions